Superior visible light hydrogen evolution of Janus bilayer junctions via atomic-level charge flow steering - Li, Jie; Zhan, Guangming; Yu, Ying; Zhang, Lizhi (Nature communications, 2016)
Although photocatalytic hydrogen evolution (PHE) is ideal for solar-to-fuel conversion, it remains challenging to construct a highly efficient PHE system by steering the charge flow in a precise manner. Here we tackle this challenge by assembling 1T MoS 2 monolayers selectively and chemically onto (Bi 12 O 17 ) end-faces of Bi 12 O 17 Cl 2 monolayers to craft two-dimensional (2D) Janus (Cl 2 )-(Bi 12 O 17 )-(MoS 2 ) bilayer junctions, a new 2D motif different from van der Waals heterostructure. Electrons and holes from visible light-irradiated Bi 12 O 17 Cl 2 are directionally separated by the internal electric field to (Bi 12 O 17 ) and (Cl 2 ) end-faces, respectively. The separated electrons can further migrate to MoS 2 via Bi–S bonds formed between (Bi 12 O 17 ) and MoS 2 monolayers. This atomic-level directional charge separation endows the Janus bilayers with ultralong carrier lifetime of 3,446 ns and hence a superior visible-light PHE rate of 33 mmol h −1 g −1 . Our delineated Janus bilayer junctions on the basis of the oriented assembly of monolayers presents a new design concept to effectively steer the charge flow for PHE. The efficiency of photocatalytic hydrogen evolution is impeded by the inability of semiconductors to precisely steer the charge flow. Here, the authors address this issue by designing conceptually new Janus bilayer junctions.